2022
DOI: 10.3389/fgene.2022.885651
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Whole-Transcriptome RNA-Seq Data Reveals the Involvement of Alternative Splicing in the Drought Response of Glycyrrhiza uralensis

Abstract: Alternative splicing (AS) is a post-transcriptional regulatory mechanism that increases protein diversity. There is growing evidence that AS plays an important role in regulating plant stress responses. However, the mechanism by which AS coordinates with transcriptional regulation to regulate the drought response in Glycyrrhiza uralensis remains unclear. In this study, we performed a genome-wide analysis of AS events in G. uralensis at different time points under drought stress using a high-throughput RNA sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…These results suggested that AS can work together with expression regulation to contribute to abiotic stress responses. Nevertheless, some studies indicated that AS might function independently to gene expression under abiotic and biotic stresses ( Gu et al., 2019 ; Ma et al., 2019 ; Ma et al., 2020 ; Li et al., 2022a ). Thereafter, the exact relationship between AS and expression level in response to stress needs to be further investigated in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that AS can work together with expression regulation to contribute to abiotic stress responses. Nevertheless, some studies indicated that AS might function independently to gene expression under abiotic and biotic stresses ( Gu et al., 2019 ; Ma et al., 2019 ; Ma et al., 2020 ; Li et al., 2022a ). Thereafter, the exact relationship between AS and expression level in response to stress needs to be further investigated in detail.…”
Section: Discussionmentioning
confidence: 99%
“…The heat shock transcription factors, HSFA1D and HSFA6B , were induced to produce different isoforms by AS under drought and heat stresses in wheat ( Liu et al., 2018 ). WRKY19 and WRKY20 were also prone to generate corresponding isoform under drought stress in G. uralensis ( Li et al., 2022a ). A DAS gene ( MSTRG.22572 ) encoding myb domain protein 59 was identified in responding to ABA stress.…”
Section: Discussionmentioning
confidence: 99%
“…Attaining high-quality raw sequencing data necessitates the elimination of low-quality reads, which contain sequences with high “N” and short reads. To screen out low-quality bases, SeqPrep ( https://github.com/jstjohn/SeqPrep ) and Sickle ( https://github.com/najoshi/sickle ) were used ( Li et al, 2022 ). We used the reference genome for the species name: Glycyrrhiza_uralensis Reference genome Version: riken (Reference Genome Source: http://ngs-data-archive.psc.riken.jp/Gur-genome/index.pl ).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of AS cases are caused by SE, while only 0.01% are caused by RI; in contrast, RI is the most common form of AS in Arabidopsis and maize ( Daszkowska-Golec et al, 2017 ; Laloum et al, 2018 ; Thatcher et al, 2016 ). However, in recent years, SE and RI are the most prevalent AS in licorice and soybeans because of advances in sequencing technology and detection tools ( Li et al, 2022 ; Song et al, 2020 ). The number of genes with introns that undergo alternative splicing in Arabidopsis thaliana ( Marquez et al, 2012 ) will increase as more transcriptome data from plants in different developmental conditions and environmental conditions are collected.…”
Section: Introductionmentioning
confidence: 99%
“…G. uralensis , a perennial herb of the legume family, is commonly used as a food sweetener, tobacco flavoring agent, and Chinese medicine ( Dang et al., 2021 ; Zhang et al., 2022 ; Bi et al., 2022 ). Due to its wide cultivation in arid and semi-arid desert steppes and edges, the yield of G. uralensis has been severely reduced ( Li et al., 2022 ; Liu et al., 2022 ). Thus, it is of considerable economic and social importance to develop an effective method for improving the drought tolerance of cultivated G. uralensis .…”
Section: Introductionmentioning
confidence: 99%